Meta‐analyses of randomized controlled trials reporting the effect of home foot temperature monitoring, patient education or offloading footwear on the incidence of diabetes‐related foot ulcers. Issue 8 (8th June 2020) - Alahakoon, C.; Fernando, M.; Galappaththy, C.; Matthews, E. O.; Lazzarini, P.; Moxon, J. V.; Golledge, J.
Abstract: Aim: The aim of this study was to perform an up‐to‐date systematic review and meta‐analysis of randomized controlled trials (RCTs) examining the efficacy of home foot temperature monitoring, patient education and offloading footwear in reducing the incidence of diabetes‐related foot ulcers. Methods: A literature search was performed using MEDLINE, PubMed, CINAHL, Scopus and Cochrane databases to identify relevant original studies. Meta‐analyses were performed using intention‐to‐treat principals for worst (main analysis) and best (sub‐analysis) case scenarios. Leave‐one‐out sensitivity analyses were used to assess the consistency of findings. Results: Of 7575 unique records, 17 RCTs involving 2729 participants were included. Four tested home foot temperature monitoring ( n = 468), six examined patient education ( n = 823) and seven assessed offloading footwear ( n = 1438). Participants' who performed home foot temperature monitoring [odds ratio (OR) 0.51, 95% confidence interval (CI) 0.31 to 0.84; n = 468] and those provided offloading footwear (OR 0.48, 95% CI 0.29 to 0.80; n = 1438) were less likely to develop a diabetes‐related foot ulcer. Patient education programmes did not significantly reduce diabetes‐related foot ulcer incidence (OR 0.59, 95% CI 0.29 to 1.20; n = 823). Sensitivity analyses suggested that offloading footwear findings were consistent, but home foot temperature findings were dependent on the individual inclusion of one trial. All RCTs had either high or unclear risk of bias. Conclusion: This meta‐analysis suggests that offloading footwear is effective in reducing the incidence of diabetes‐related foot ulcers. Home foot temperature monitoring also appears beneficial but larger trials are needed (PROSPERO registration no.: CRD42019135226). What's new?: Diabetes‐related foot ulcers are common and precipitated by high plantar pressures that stimulate localized foot inflammation and subsequent ulcer development. Previous meta‐analyses have suggested that home foot temperature monitoring and offloading footwear, but not patient education, reduce diabetic foot ulcer incidence. This meta‐analysis incorporated data from 17 randomized clinical trials including two not included in previous pooled data analyses. Offloading footwear [odds ratio (OR) 0.48, 95% confidence interval (CI) 0.29 to 0.80; n = 1438] and home foot temperature monitoring (OR 0.51, 95% CI 0.31 to 0.84; n = 468), but not patient education (OR 0.59, 95% CI 0.29 to 1.20; n = 823) reduced the incidence of diabetes‐related foot ulcers. Findings for offloading footwear, but not home foot temperature monitoring were consistent in sensitivity analyses. People at high risk of diabetes‐related foot ulcers should be offered offloading footwear. Home foot temperature monitoring appears efficacious but larger trials are needed.